Effect of Nano-Selenium on Nutritional Quality of Cowpea and Response of ABCC Transporter Family - Li Li; Yuzhou Xiong; Yuan Wang; Shuai Wu; Chunmei Xiao; Shiyan Wang; Shuiyuan Cheng; Hua Cheng (Molecules, 2023)
It is an important way for healthy Selenium (Se) supplement to transform exogenous Se into organic Se through crops. In the present study, Vigna unguiculata was selected as a test material and sprayed with biological nano selenium (SeNPs) and Na2SeO3, and its nutrient composition, antioxidant capacity, total Se and organic Se content were determined, respectively. Further, the response of ABC transporter family members in cowpea to different exogenous Se treatments was analyzed by transcriptome sequencing combined with different Se forms. The results show that the soluble protein content of cowpea increased after twice Se treatment. SeNPs treatment increased the content of cellulose in cowpea pods. Na2SeO3 treatment increased the content of vitamin C (Vc) in cowpea pods. Se treatments could significantly increase the activities of Peroxidase (POD), polyphenol oxidase (PPO) and catalase (CAT) in cowpea pods and effectively maintain the activity of Superoxide dismutase (SOD). SeNPs can reduce the content of malondialdehyde (MDA) in pods. After Se treatment, cowpea pods showed a dose-effect relationship on the absorption and accumulation of total Se, and Na2SeO3 treatment had a better effect on the increase of total Se content in cowpea pods. After treatment with SeNPs and Na2SeO3, the Se species detected in cowpea pods was mainly SeMet, followed by MeSeCys. Inorganic Se can only be detected in the high concentration treatment group. Analysis of transcriptome data of cowpea treated with Se showed that ABC transporters could play an active role in response to Se stress and Se absorption, among which ABCB, ABCC and ABCG subfamilies played a major role in Se absorption and transportation in cowpea. Further analysis by weighted gene co-expression network analysis (WGCNA) showed that the content of organic Se in cowpea treated with high concentration of SeNPs was significantly and positively correlated with the expression level of three transporters ABCC11, ABCC13 and ABCC10, which means that the ABCC subfamily may be more involved in the transmembrane transport of organic Se in cells.